Cardinal Temperatures of Brassica sp. and How to Determine It - SUANDA, D. K. SUANDA (Agrotrop : Journal on Agriculture Science; Vol 2 No 1 (2012), 2013)
Cardinal temperatures consist of minimum, optimum and maximum of plant growth, and might be able to be determined by assessing effect of temperature on seed germination. An experiment of seed germination was conducted in laboratory, using thermal gradient plate for ten days. To test hypothesis that rapeseed genotypes vary in their response to temperatures. The design of this experiment was a split plot with four replications. The main-treatments were 14 different temperatures: 0.4°C, 3.3°C, 7.8°C, 11.6°C, 13.3°C, 15.0°C, 16.8°C, 18.3°C, 20.9°C, 21.1°C, 25.6°C, 29.0°C, 33.0°C and 36.3°C. Sub-treatments were 6 brassica genotypes: Brassica napus genotypes (Tatyoon and Marnoo); B. campestris (Jumbuck and Chinoli B); B. juncea (No. 81797 and Zero Erusic Mustard (ZEM) 2). Each treatment was using 50 seeds. Germinations were observed daily for ten days and data were analyzed with regression and correlation. Genotypes responded differently to temperatures with Jumbuck the most sensitive to low temperature with minimum temperature (7.90°C), then respectively followed by Chinoli B (6.36°C), ZEM 2 (4.77°C), Tatyoon (4.63°C), No. 81797 (2.59°C), and Marnoo (1.00°C). For high temperature the most sensitive was No. 81797 with maximum temperature 38.61°C. and then respectively followed by Marnoo (39.76°C), Chinoli B (42.93°C), Tatyoon (43.79°C), Jumbuck (44.58°C) and ZEM 2 (45.88°C). Optimum temperatures were for Jumbuck was 24.56°C, ZEM 2 (26.95°C), Tatyoon (27.12°C), No. 81797 (28.12°C), Chinoli B (29.74°C) and Marnoo (30.48°C).
Keywords: cardinal temperature, Brassica sp., thermal gradient plate